The Pugs and the Elephant: Dr Botkin and the Professional and National Identity of Physicians in the Russian Court. (11th September 2017) - Sopo, Elina
Summary: This essay explores lesser-known members of the Russian court's medical community and the printed press to trace information on the working environment, events and attitudes surrounding the 'Great Russian Asclepios', Sergei Botkin. It first shows how the changing intellectual atmosphere (from slavophilism to nihilism) affected the course of events inside the sphere of court medicine when Nicholas I's era turned into a reform era. Then it demonstrates how Botkin and his fellow physicians balanced their professional autonomy with their service to the central state, reveals some of the medical community's archetypes and finally identifies the opposing medical forces around Botkin. Resisting professional and political attempts at isolation and court intrigues, Botkin really came to personify the main events of the era. The medical community of the court is viewed here as a micro-cosmos of the professional peculiarities observed elsewhere in the medical community of Tsarist Russia.